2019
DOI: 10.3390/md17030137
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biocompatibility Properties of Type I Collagen from the Skin of Nile Tilapia (Oreochromis niloticus) for Biomedical Applications

Abstract: The aim of this study is to investigate the physicochemical properties, biosafety, and biocompatibility of the collagen extract from the skin of Nile tilapia, and evaluate its use as a potential material for biomedical applications. Two extraction methods were used to obtain acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) from tilapia skin. Amino acid composition, FTIR, and SDS-PAGE results showed that ASC and PSC were type I collagen. The molecular form of ASC and PSC is (α1)2α2. The FTIR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 73 publications
5
41
0
Order By: Relevance
“…But there are still many problems that limit the application of collagen hydrogels, especially low mechanical strength making it unsuitable as a block gel [36]. Hou et al [37,38] have proved that the tilapia collagen showed high biocompatibility and they prepared a composite material using tilapia collagen with konjac glucomannan, which significantly improved its mechanical properties. Although the addition of the second component can significantly improve the mechanical strength of the collagen material, it may decrease the function of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…But there are still many problems that limit the application of collagen hydrogels, especially low mechanical strength making it unsuitable as a block gel [36]. Hou et al [37,38] have proved that the tilapia collagen showed high biocompatibility and they prepared a composite material using tilapia collagen with konjac glucomannan, which significantly improved its mechanical properties. Although the addition of the second component can significantly improve the mechanical strength of the collagen material, it may decrease the function of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports have confirmed that collagens from different raw materials may have varying structures and characteristics, and exhibit very different fibril formation abilities, which have limited their wide-spread use. Fish collagen has a similar amino acid composition as conventional collagens with a decreased amount of imino acid and increased serine and threonine, and carries no disease risk [25]. To the best of our knowledge, there have been few reports comparing the characteristics of collagen from different puffer species.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of collagen obtained from tilapia skin showed that as well as acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) have typical type I collagen features. The ASC denaturation temperature was 36.1 °C, but for PSC it was 34.4 °C [ 51 ]. Whereas isolated acid-soluble collagen from the skin of silver carp ( Hypophthalmichthys molitrix ) also comprised type I collagen as shown by SDS-PAGE patterns [ 52 , 53 ], with denaturation temperature established at around 29 °C for ASC.…”
Section: Types Of Collagen In Cosmeticsmentioning
confidence: 99%